2014
DOI: 10.1620/tjem.234.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Pulsed Current Stimulation Enhances Wound Healing in Diabetic Rats by Restoring the Expression of Collagen, <i>α</i>-Smooth Muscle Actin, and TGF-<i>β</i>1

Abstract: Impaired wound healing is a common complication of diabetes mellitus and a major morbidity that leads to pain and severely diminished quality of life. Diabetic wounds are commonly associated with defective immune cell responses or abnormality of extracellular matrix. Various types of electrical stimulation interventions have been used to promote tissue healing. However, it is unclear whether high-voltage pulsed current stimulation (HVPCS) enhances diabetic wound healing. In this study, the effects of HVPCS on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 18 publications
(19 reference statements)
0
28
0
7
Order By: Relevance
“…DC, AC, and PC have exhibited highly differential effects on fibroblasts in an in vitro study, where at high intensity and frequencies, the PC maximally downregulates collagen I and have a lower cytotoxic effect than AC and DC 13. At the wound site, enhanced fibroblast activities with DC, PC, and HVPC have also been reported in vivo, resulting in an increased fibroblast number,29,39 collagen synthesis,13,29,33,36,38 myofibroblast creation, and tensile strength 29. HVPC on diabetic rats has shown accelerated wound healing and restoration of the expression levels of collagen I and transforming growth factor, suggesting reactivation of the fibroblast activities 33.…”
Section: Es Cellular and Molecular Mechanismsmentioning
confidence: 96%
“…DC, AC, and PC have exhibited highly differential effects on fibroblasts in an in vitro study, where at high intensity and frequencies, the PC maximally downregulates collagen I and have a lower cytotoxic effect than AC and DC 13. At the wound site, enhanced fibroblast activities with DC, PC, and HVPC have also been reported in vivo, resulting in an increased fibroblast number,29,39 collagen synthesis,13,29,33,36,38 myofibroblast creation, and tensile strength 29. HVPC on diabetic rats has shown accelerated wound healing and restoration of the expression levels of collagen I and transforming growth factor, suggesting reactivation of the fibroblast activities 33.…”
Section: Es Cellular and Molecular Mechanismsmentioning
confidence: 96%
“…The previous study revealed that ES could reduce inflammation, improve blood flow, reduce the bacterial burden, reduce pain and edema, decrease muscle spasms, and improve TGF-β1, collagen-I, and muscle contraction (Demir, Balay and Kirnap, 2004;Sebastian et al, 2011;Kim, Cho and Lee, 2014;Torkaman, 2014). Recent research by the author has shown that compared with the standard treatment, wounds treated with ES showed a reduction in inflammation and an increase in re-epithelialisation (Sari, Sutrisna and Hartono, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in inflammation following ES in diabetic ulcers might be due to the ability of ES to enhance phagocytosis (Cho et al, 2000). The improvement of reepithelialization might be due to the ability of ES to promote keratinocyte migration (Kim, Cho and Lee, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations